Price Perception, Service Quality, and Price Affordability as Predictors of Customer Satisfaction in Ride-Hailing Services: Evidence from Maxim Users in Bandar Lampung, Indonesia - Roni Saputra; Raditia Tirta Pandu; Muhammad Efendi; Febrianty Febrianty; Reza Hardian Pratama (International Journal of Business, Law, and Education, 2026)
Digital transformation has reshaped urban mobility by enabling app-based ride-hailing services that offer real-time access, flexible ordering, and transparent fare information. In Indonesia, Maxim has become one of the ride-hailing platforms associated with competitive pricing and affordability-oriented service positioning. This study examines the influence of price perception, service quality, and price affordability on customer satisfaction among Maxim users in Bandar Lampung, Indonesia. A quantitative associative design was applied using survey data from 100 respondents selected through purposive sampling. Respondents were Maxim users who had used the service more than once. The data were analyzed using partial least squares structural equation modeling (PLS-SEM). The measurement model results indicate acceptable convergent validity and reliability, with indicator loadings above the recommended threshold, Cronbach’s alpha values ranging from 0.812 to 0.890, composite reliability values ranging from 0.865 to 0.920, and average variance extracted values exceeding 0.50. The structural model shows that service quality has a positive and significant effect on customer satisfaction (β = 0.510, t = 4.821, p < 0.001), price affordability has a positive and significant effect on customer satisfaction (β = 0.325, t = 3.144, p = 0.002), and price perception has a positive and significant effect on price affordability (β = 0.605, t = 7.410, p < 0.001). The model explains 65.4% of the variance in customer satisfaction and 36.0% of the variance in price affordability. These findings suggest that customer satisfaction in ride-hailing services is shaped not only by low prices but also by the extent to which users perceive the fare as reasonable, affordable, and supported by reliable service quality.